TBM in Azad Kashmir region of Pakistan: in situ stress measurements for rockburst prevision. Issue 1 (1st August 2018) - Amici, Riccardo; Peach, Gary; Nadeem, Mohammed
Abstract : Using the authors' experience, this paper details the in situ stress measurements in twin tunnel boring machine (TBM) tunnels of the Neelum Jhelum hydropower project, located in the Azad Kashmir region of north-east Pakistan in foothills of the Himalayas, with overburdens up to 2000 m and high tectonic stresses in very complex geology. The ability to predict the likelihood, location, severity and number of rockbursts directly impacts on the tunnel safety and daily production rates. This, combined with the lack of previous project experience in similar conditions, has required the use of all the available advanced geological prediction methods: forward probing, tunnel seismic tomography, continuous microseismic monitoring and in situ stress measurements were used. These methods, except in situ stress measurements, only gave an indication of likelihood and severity of rockbursts. The in situ tests provided the actual ground stresses and their orientations. The in situ stress results contradicted the forecasts based on the classical empirical rules combining stress analysis and rock strength. This paper is focused on the in situ stress measurements carried out behind the two TBMs and details the information obtained and how data were interpreted and integrated to support excavation, prevention and control of rockbursts, which improved tunnel safety and productivity.